Effect of Intercropping Patterns on Seed Yield and Its Attributing Parameters in Onion Seed Crop - NITESH KUMAR; SK DHANKHAR; MONIKA YADAV (Seed Research, 2026)
The present investigation entitled “Effect of intercropping patterns on seed yield and its attributingparameters in onion (Allium cepa L.) seed crop” was carried out at Research Farm of the Department of VegetableScience, CCS Haryana Agricultural University, Hisar during season of 2018-19. The experimental treatments viz.,T1-onion seed crop (sole ) 60 X 60 cm , T2-palak (sole) 15 X 5cm, T3-methi (sole) 20 X 10 cm , T4-onion + palak(one row) T5- onion + palak (two rows), T6- onion + palak (three rows), T7- onion + palak (broadcasting), T8- onion+ methi (one row), T9- onion + methi (two rows) and T10- onion + methi (broadcasting) were laid out in a RandomizedBlock Design (RBD) with three replications. Based on the research investigation it was found that onion seed crop(sole crop) recorded maximum number of seeds umbel-1 (1198.33), seed weight umbel-1 (4.15 g), number ofseeds per plant (8253.33), seed weight plant-1 (26.45g) and seed yield ha-1 (6.16 q ha-1 ), which was significantlyhigher than rest of the intercropping treatments. The higher test weight was recorded for onion seed sole crop(3.85g) while lowest was obtained with onion + palak broadcasting (3.78 g). Within intercropping system, thenumber and weight of seed umbel-1 were appreciably higher in onion + methi (one row) followed by onion + palak(one row). Whereas, the seed yield plant-1 significantly improved in onion + palak (one row) followed by onion +methi (one row).